The law applicable to the dismissal in the international employment contract - Gómez Abelleira, Francisco Javier (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
Dismissals are an important source of litigation in the international employment contract. This article addresses the issue of determining the law applicable to dismissals within the framework of the Rome I Regulation and analyzes the specialties of dismissal of expatriates under Spanish law, including the application of overriding mandatory provisions in Spain